Irvinga L. Janisa teoria podejmowania złych decyzji w samorządzie terytorialnym, spółdzielczości i ruchach społecznych. Perspektywa socjologiczna - Moczuk, Eugeniusz (PRAWO i WIĘŹ, 2026)
The aim of this study is to demonstrate how Irving L. Janis’s groupthink and bad decision-making are analyzed within sociology of law, as well as what their potential consequences may be in local government, cooperatives, and social movements. The analysis of this issue indicates that Irving L. Janis, in his analytical interpretation of groupthink, drew attention to certain regularities existing within groups, including the tendency to strive for consensus within the group becoming so strong that it suppresses realistic alternative assessments and critical thinking. The characteristics of groupthink syndrome include: a) the illusion of omnipotence, invincibility, infallibility, and self-confidence; b) group efforts to rationalize one’s own actions; c) an unquestioned belief in the group’s morality and professional ethics; d) stereotyping opponents of a given problem solution and treating them as enemies; e) direct pressure on group members to enforce compliance and conformist behavior; f) self-censorship of deviations from group consensus; g) a shared illusion of unanimity; h) the emergence of individuals who filter information and censor bad information.